Acute Localized Abdominal Pain From Primary Epiploic Appendagitis - Hiroaki Nakagawa; Yasushi Miyata (Annals of Internal Medicine: Clinical Cases)
This report describes primary epiploic appendagitis in a 40-year-old man. He had the classic physical finding of highly localized abdominal pain and the classic computed tomography findings of a hyperattenuating ring sign and a central dot sign.